Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1057/s41287-020-00299-4
|View full text |Cite
|
Sign up to set email alerts
|

“Our Generation…” Aspiration, Desire, and Generation as Discourse Among Highly Educated, Portuguese, Post-austerity Migrants in London

Abstract: Drawing on 18 months of multi-sited ethnographic fieldwork, this paper brings into dialogue empirical material from young, highly educated Portuguese migrants in London, theoretical work on desire in migration studies and sociological approaches to theorising aspirations. The paper argues that young migrants' narratives of migration shed important light on the working of aspirations in the processes of becoming through migration. Such orientations towards the future are shaped by young migrants' engagements wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The idea of generation as life-phase illuminates how migration is related to the construction and performativity of youth. This approach sheds light on the interplay between institutional dynamics which make migration a likely option during certain points in the youth phase of the life-course (Ní Laoire 2000), and young people's desire to migrate or stay put in order to enact a particular generationed identity (Hertrich and Lesclingand 2013;Rodan and Huijsmans 2021). From an institutional perspective, labour markets and the provision of education are typically more developed and diverse in urban settings than in rural areas.…”
Section: Youth Migration and Diverse Interpretations Of Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of generation as life-phase illuminates how migration is related to the construction and performativity of youth. This approach sheds light on the interplay between institutional dynamics which make migration a likely option during certain points in the youth phase of the life-course (Ní Laoire 2000), and young people's desire to migrate or stay put in order to enact a particular generationed identity (Hertrich and Lesclingand 2013;Rodan and Huijsmans 2021). From an institutional perspective, labour markets and the provision of education are typically more developed and diverse in urban settings than in rural areas.…”
Section: Youth Migration and Diverse Interpretations Of Generationmentioning
confidence: 99%
“…A Mannheimian interpretation of generation draws attention to how widespread involvement in migration among youth can become a feature in how people identify with others in their generation and as a generation (Rodan and Huijsmans 2021). This perspective draws on Karl Mannheim's seminal work (Mannheim 1952) on the role of generations in social change.…”
Section: Youth Migration and Diverse Interpretations Of Generationmentioning
confidence: 99%
“…Barford et al (2021) found that youth "in waiting" adapt to changing social contexts both on their own or by relying on social network support. In other studies, waiting youth preoccupy themselves with playing, talking, scheming, or working in order to derive some benefits from waiting or simply to keep their minds "off the stresses" (Stasik et al, 2020;Rodan & Huijsmans, 2021;Zharkevich, 2020). A range of concepts point to the strategies youth in the Global South use to cope with waiting: "killing time" and "building solidarity" (Ralph, 2008), doing "timepass" (Jeffery, 2010), "hustling to survive" (Munive, 2010), and "zigzagging'' or meandering through available opportunities and forms of entrepreneurship (Jeffery & Dyson, 2013).…”
Section: Youth In "Waithood"mentioning
confidence: 99%
“…Much of the existing literature on European youth mobilities focuses on migration to more advanced economies as part of a strategy of income or career advancement (King, Lulle, et al, 2018; Lulle et al, 2021). Indeed, particular attention has been paid to youth migration from Mediterranean countries (Montanari & Staniscia, 2017; Rodan & Huijsmans, 2021). However, some young working migrants use mobility to Southern Europe (King, 2019; Seers et al, 1979) to opt out of the pressures embedded in mainstream ideas of progression and success.…”
Section: Introductionmentioning
confidence: 99%